Deformation dynamics of particle-laden bubbles: The effect of surfactant concentration and particle contact angle. (1st January 2021) - Wang, H.; Brito-Parada, P.R.
Highlights: The fast deformation of silica particle-laden bubbles was studied. Surface pressure at the deforming particle-laden bubbles was determined. 0.2 μM dodecylamine has negligible effect on the surface pressure at the deforming bubbles. 20 μM dodecylamine significantly decreases the deformation of the bubbles. The change in particle contact angle changes the surface pressure. Abstract: The pinch-off dynamics of bubbles coated with silica particles in deionised water and in dodecylamine (DDA) solution, at 0.2 μM and 20.0 μM, was studied using high-speed photography. Surface pressure generated at the deforming particle-laden interface during bubble pinch-off was obtained based on the fitting to a pinch-off model. It was observed that the pinch-off dynamics of these particle-laden bubbles remained almost unchanged at the low DDA concentration of 0.2 μM, while the dynamics slowed down significantly at the DDA concentration of 20.0 μM. Notably, both the 0.2 μM and 20.0 μM DDA concentrations have a negligible effect on the surface tension and pinch-off dynamics of uncoated bubbles. The difference in DDA concentration, however, is known to change the contact angle of silica particles from approximately 27° to 45°. It can be concluded that it is the change in particle contact angle that affects the pinch-off dynamics of particles-laden bubbles. Indeed, at a concentration of 0.2 μM DDA there is no significant change in contact angle of the silica particles with respect to that in DI water only, resulting in similar dynamics. It is suggested that the increase in the particle contact angle changes particle interactions, leading to a change in the surface pressure and apparent surface tension of particle-laden bubbles, which in turn slows down the pinch-off process. The findings in this work are relevant to our understanding of fundamental aspects of deforming particle-laden interfaces, such as those in the coalescence of flotation froths.